Effect of a Flipped Classroom Compared With a Traditional Lecture on Physician Assistant Students' Exam Performance. Issue 4 (2nd December 2021) - Wright, Matthew; Jia, Yuane; Vidal, Erich; O'Connell, Claire Babcock; Palfreyman, Lori; Parrott, J. Scott
Abstract : Purpose: The purpose of this study was to retrospectively compare the exam performance of physician assistant (PA) students given asthma instruction in a flipped classroom with PA students in a traditional lecture setting while controlling for students' previous academic performance and clinical asthma experience. Methods: Three cohorts of PA students (n = 146) from the years 2017 (traditional-lecture setting) and 2018 and 2019 (flipped-classroom setting) were included in the study. Academic performance across cohorts was compared using answers to 11 exam questions reflective of the asthma content. Results: Findings demonstrated significantly greater performance in the flipped classroom compared with traditional lecture. The 2018 and 2019 cohorts scored 9.4% and 13.2% higher, respectively, compared with the 2017 cohort. Exam performance of students with a low likelihood of clinical exposure to asthmatic patients before PA school was similar to those with a high likelihood. Conclusion: This study found improved exam performance with a flipped classroom. The flipped classroom represents a potential opportunity to maximize similar performances by both less experienced students and more experienced students.